Characterization of Four Copper Materials for Application as Reference Materials for High Precision Copper Isotope Analysis by Laser Ablation Inductively Coupled Plasma Multi-Collector Mass Spectrometry - Yang, Zhaoping; Jackson, Simon Edward; Skulski, Thomas (Frontiers in Chemistry, 2021)
We have investigated the suitability of four Cu metal materials, SSC-1, SSC-3 and SSC-4 and CUPD-1, originally developed by the Canada Centre for Mineral and Energy Technology as certified reference materials for trace element analysis, as Cu isotope standard reference materials for solution nebulization (SN) and LA-MC-ICP-MS analysis of Cu. The Cu isotopic composition and homogeneity of these four materials were characterised by SN- and LA-MC-ICP-MS, and are reported for the first time. The bulk Cu isotopic compositions (expressed as δ65CuSRM976 in per mil (‰) relative to National Institute of Standards and Technology NIST SRM976 with 2 s.d. uncertainties) of SSC-1, SSC-3 and SSC-4, determined utilizing SN-MC-ICP-MS, are identical within analytical uncertainty at 0.03 ± 0.04‰ (n = 29), 0.04 ± 0.03‰ (n = 28), and 0.05 ± 0.05‰ (n = 29), respectively; the composition of CUPD-1 is 2.14 ± 0.06‰ (n = 28). The compositions are 0.01 ± 0.05 ‰ (n = 29), 0.04 ± 0.04‰ (n = 29), 0.03 ± 0.03‰ (n = 28) and 2.15 ± 0.04‰ (n = 28), respectively, relative to the European Reference Material ERM®-AE633 Cu isotope standard. The Cu isotope homogeneity of the four new reference materials was assessed by determining whether multiple individual in situ Cu isotope measurements made by LA-MC-ICP-MS analysis (43 µm spot size), using each of the other three reference materials as a calibrator, approximated a single normal distribution. Normality tests show that: (1) the Cu isotope data acquired on SSC-1, SSC-3, SSC-4 and CUPD-1 do not depart significantly from a normal distribution, and (2) there are no other significant sources of scatter; e.g. heterogeneity of the reference materials. The mean δ65CuSRM976 values determined by LA-MC-ICP-MS for SSC-1, SSC-3, SSC-4 and CUPD-1 are in agreement with those determined by SN-MC-ICP-MS analysis at the 95% confidence level and have excellent precision (2 s.d. ≤ 0.10‰). These results suggest that SSC-1, SSC-3, SSC-4 and CUPD-1 can be considered isotopically homogeneous at a spatial resolution of 43 µm, and they are suitable reference materials for calibration and quality control of in situ and SN Cu isotope analyses of Cu.